Building a learning network to accelerate improvement in pancreas cancer care and outcomes: Canopy Cancer Collective. Issue 28 (1st October 2022) - Herman, Joseph M.; Stricker, Carrie Tompkins; Myers, Sarah; Korah, Bobby; Narang, Amol; Hacker-Prietz, Amy; Deperalta, Danielle; Hong, Theodore S.; Dullard, Amy; Lowy, Andrew; Ejaz, Aslam; Tempero, Margaret A.; et al.
Abstract : 368 Background: Pancreas cancer (PC) survival is among the lowest of all malignancies. While limited advances in treatment are a major driver of this reality, ample opportunity exists to improve outcomes by reducing care variation, providingcoordinated, comprehensive care, and accelerating research. Learning health networks (LHNs) improve outcomes in pediatric diseases through such mechanisms, yet are not widely implemented in adult care. We aimed to develop, implement, and collect initial outcomes of the first oncology LHN, the Canopy Cancer Collective (CCC). Methods: In 2019, we established CCC to apply to PC the LHN model, including core tenets of continuous quality improvement (QI), data-sharing, empowered interdisciplinary teams and a stakeholder community including individuals with PC, and focus on community-defined improvable "outcomes that matter". Six care centers were selected to join the LHN, and engaged in a collaborative design process to co-create a set of improvement aims and change ideas. Center team members received training in basic QI methods/tools guided by the IHI Model for Improvement and were coached to apply these to local improvement efforts. LHN infrastructure and technology enabled sharing of new ideas, best practices, and results amongst centers. Eight more centers joined in 2021, and an outcomes database built and implemented. Results generated by this database will inform center-specific and Network-wide improvement efforts and allow the LHN to undertake research. Results: Currently, 14 care centers are active participants in the CCC LHN. Five key outcomes have been defined as key targets, and centers have co-created and tested change ideas organized around key drivers of excellent PC care including proactive, timely care, aligned/prepared multidisciplinary teams, informed, activated patients, and accurate diagnosis and disease classification. 100% of care centers are trained in QI methods and actively testing change ideas. For example, in May 2022, 11 centers reporting on monthly QI activities met on average 4 times to advance QI projects, deploying a mean of 2.9 plan-do-study-act (PDSA) cycles (range, 0-5) focused on key drivers and outcomes, including reduced time to treatment, increased trial enrollment, assessment of patient experience, and improved data capture. Conclusions: Building a sustainable LHN for PC centers is feasible and has set the stage for improving patient and provider outcomes through iterative community-building, continuous improvement, and sharing of data and multidisciplinary best practices. Results lay the foundation for expansion not only in PC, but translation to other complex malignancies that will benefit from transformative, system-based approaches to outcome improvement.